Impact of Unethical Pro-Leader Behavior on Careerism Through Co-worker Undermining - Riffat Gill; Sadia Shaheen; Muhammad Farooq Rehan (Sustainable Business and Society in Emerging Economies)
Purpose: Drawing upon sense-making theory, this study aims to examine the impact of unethical pro-leader behavior (UPLB) on careerism. Specifically, it explores the mediating role of co-worker undermining in this relationship.